الاعتدال في الخطاب السياسي وأثره في بناء الهوية الوطنية العراقية (قضايا سياسية, 2022)
This brief study attempts to show the effect of moderation in political discourse as a verbal behavior practiced in building and strengthening the Iraqi national identity (political identity). There is a relationship between the nature of political discourse and the nature of identity. Accordingly, the study showed the meanings of moderation, discourse and identity, the pillars of Iraqi identity and its challenges in a descriptive and analytical context of this problem, and how to solve it by emphasizing the necessity of moderation in the discourse in order to move into the national discourse instead of the discourse of sub-identities.